ANALISIS EKSERGI PADA UNIT DISTILASI ATMOSFERIK DAN VAKUM MINYAK BUMI - Zikri, Ahmad (KINETIKA, 2014)
The atmospheric and vacuum distillations are the first plant in a crude oil refinery, in which several intermediate product  are  obtained  through  distillation of  the  crude  oil  mixture.  To  increase  the  thermodynamic  efficiency,  we need  to  use  both  the  temperature-enthalpy  and  exergy  losses  together.  It  is  important  to  determine  the  exergy losses profiles and to analyze the distribution losses in all stage of distillation column. Aspen Plus software is used as  assistance  to simulate  changes  in  the  given  circumstances.  The  results  of  the  exergy  and  exergoeconomic analyses  are  presented  in  this  paper.  The  important  unit  in  this  analysis  are  distillation  column  operating conditions,  crude  heating  furnace,  and  supporting  Heat  Exchanger.  In  this  study,  atmospheric  and  vacuum distillation  columns  at  refineries  UP-III-Plaju  Indonesia  become  the  case  study.  The proposed  method  is  to condition  the  feed  temperature  limits  vary  with  the  quality  of  the  resulting  products  were  unchanged.  The  fuel requirement  would  be  decreased,  as  well  as  the  temperature  which  is  result  by  crude  heating  furnace.  In atmospheric distillation column, about 0.6 % (0.25 T/D) and 20.8 % (8.9 T/D) for vacuum distillation is direct fuel can be derived. With this analysis we can save operating cost approximately 1.4 million U.S. $ per year.